The Anglo-Boer War in the despatches of Russian military attachés (Historia, 2021)
With  the encouragement and support of  the University of  South Africaand in  particular, of  Professor S. Pauw, the University's Principal,  I  under-took a  tour  of  Europe and America to  study modern methods of  teachingRussian.  During  my  travels  I  visited  Washington D.C.  in  January, 1962and there  I  met Dr.  S.  Yakobson who  is  in  charge of  the Slavic  Sectionof  the  Library    of   Congress.    I   asked  him   if   he  knew  of   any  documentsgiving  information  about the  Russian attitude towards the Boers during  theAnglo-Boer War.    He  told   me  of  a  publication  he  had  seen, which hadappeared in  the  Soviet "Krassni  Arkhiv"    (Red  Archive)  during  the  lastWar, which was for the first  time printing  documents, up to  then kept secretin  the Intelligence Dept. files  (and  later transferred to  the  Historical  WarArchives).
Keywords: Anglo-Boer War; Krassni Arkhiv; Russian military